Internal audit in a multinational perspective: Problems and challenges - Brauweiler, Christian (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The need to standardize procedures and tackle similar questions of auditing, risk management, controlling and similar related topics is vast, especially, but not exclusively in multinational companies. However, smaller companies more and more find themselves in a position to act more globally – or at least internationally – in terms of sourcing as well as sales. This brings new needs for and new foci on topics as Internal Audit as well as Corruption Prevention. This article gives some ideas, hints and challenges towards these topics. In order to clarify the views expressed in this article, the author first gives some general information about internal audit, such as its definition, tasks and objectives, its historical development, legal background, structure and implementation, in order to make clear, on which aspects and understanding the argumentation is based. This introduction will provide a theoretical basis for the description and identification of the potential problems and possible challenges in an international perspective
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 474, s. 25-32
Keywords: internal audit; SME; multinational cooperation; audyt międzynarodowy; MŚP; współpraca międzynarodowa